2021
DOI: 10.1002/jmri.27879
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Networks for Automated Classification of Prostate Multiparametric Magnetic Resonance Imaging Based on Image Quality

Abstract: Background Prostate magnetic resonance imaging (MRI) is technically demanding, requiring high image quality to reach its full diagnostic potential. An automated method to identify diagnostically inadequate images could help optimize image quality. Purpose To develop a convolutional neural networks (CNNs) based analysis pipeline for the classification of prostate MRI image quality. Study Type Retrospective. Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Image quality could be improved through the use of the automated approach for identifying diagnostically poor images, for example. A CNN-based analysis pipeline to classify the prostate MRI images quality was developed in [13]. This model exhibited great accuracy in prostate MRI classification of image quality on the individual-slice basis and nearly flawless accuracy in classifying whole sequences when applied to the entire dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Image quality could be improved through the use of the automated approach for identifying diagnostically poor images, for example. A CNN-based analysis pipeline to classify the prostate MRI images quality was developed in [13]. This model exhibited great accuracy in prostate MRI classification of image quality on the individual-slice basis and nearly flawless accuracy in classifying whole sequences when applied to the entire dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Future iterations of PI-QUAL criteria are likely to include elements of lesion detection and quantification of the effect of PI-QUAL scores in clinical practice; the revision of PI-QUAL scores might create the basis of future QC processes to assess image quality 87,88 . AI might have a role to support the process of image quality assessment; results from a feasibility study showed that CNNs could be used to provide a binary classification of prostate MR images as high-quality or low-quality on an individual-slice basis with high accuracy (79.8-96.6%) and at a sequence level with almost perfect accuracy (92.3-100%) 89 . Automation of this process and calibration to PI-QUAL scoring would make central review of image quality a realistic goal and could be used at a centre level to identify poor image quality on a cases-by-case basis, to indicate whether repeating sequences is necessary.…”
Section: [H1] Components Of the Prostate Cancer Diagnostic Pathwaymentioning
confidence: 99%
“…Yet, the study of Cipollari et al 4 has some limitations. The model uses a binary classification to assess image quality, but a wider scale could be more valuable.…”
mentioning
confidence: 97%
“…Several articles have recently discussed the quality standards that should be applied to mpMRI examinations 2,3 . In this issue of JMRI , Cipollari et al 4 bring attention to a new approach to the topic.…”
mentioning
confidence: 99%